UJI PROGNOSTIK SKOR MOTORIK FREKUENSI NAFAS DAN MEMBUKA MATA M N M SKOR UNTUK MEMPREDIKSI KELUARAN DALAM TIGA HARI PADA PASIEN DEWASA TRAUMA KAPITIS SEDANGBERAT - Andrie Gunawan*, Lyna Soertidewi **, Eka Musridharta**, Joedo Prihartono*** (NEURONA, 2011)
INTRODUCTION ATTEMPT TO PREDICT PROGNOSIS AFTER CRANIOCEREBRAL INJURY IS VERY IMPORTANT AN ACCURATE INITIAL ASSESSMENT BY MEDICAL PERSONNEL ESPECIALLY ATTENDING PHYSICIAN IS NEEDED TO MAKE A RIGHT MANAGEMENT AND TO PREDICT OUTCOME INITIAL ASSESSMENT WITH SCORING TOOL IS A SIMPLEST METHOD TO ANSWER FAMILY QUESTION ESPECIALLY IN MEDICOLEGAL AND ADMINISTRATIVE ASPECTS